2015
DOI: 10.1002/ps.3988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of refuges on the evolution of resistance to transgenic corn by the western corn rootworm, Diabrotica virgifera virgiferaLeConte

Abstract: BACKGROUND Diabrotica virgifera virgifera LeConte is a major pest of corn and causes over a billion dollars of economic loss annually through yield reductions and management costs. Corn producing toxins derived from Bacillus thuringiensis (Bt) has been developed to help manage D. v. virgifera. However, previous studies have demonstrated the ability of this species to evolve resistance to Bt toxins in both laboratory and field settings. RESULTS We used an experimental evolution approach to test the refuge strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“…Additionally, in past studies, resistance to mCry3A corn did not significantly affect larval development rate in single-plant bioassays with mCry3A corn (Gassmann et al 2014). While developmental rate may not be a reliable indicator of resistance with single-plant bioassays, it may be an informative metric in other bioassay approaches such as bioassays with seedling mats , Deitloff et al 2015.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Additionally, in past studies, resistance to mCry3A corn did not significantly affect larval development rate in single-plant bioassays with mCry3A corn (Gassmann et al 2014). While developmental rate may not be a reliable indicator of resistance with single-plant bioassays, it may be an informative metric in other bioassay approaches such as bioassays with seedling mats , Deitloff et al 2015.…”
mentioning
confidence: 81%
“…Cases of resistance to Cry3Bb1 and mCry3A increase the vulnerability of some pyramids to the rapid evolution of resistance, and all current rootworm pyramids contain either mCry3A or Cry3Bb1 (Cullen et al 2013). As a result, there is the potential for western corn rootworm to adapt to Cry34/35Ab1 corn, and past laboratory studies have found that resistance to Cry34/35Ab1 corn can evolve following four generations of on-plant selection (Deitloff et al 2015).…”
mentioning
confidence: 99%
“…Recent research indicates that larval movement in several lepidopteran pest species is a threat to the blended refuge strategy [52][53][54]. Although less extensive than lepidopteran caterpillars, dispersal rate of subterranean rootworm larvae between adjacent plants is high enough [55] to potentially compromise a blended refuge strategy, as observed in laboratory evolution experiments [56]. However, in the case of D. v. virgifera, a blended refuge has the possible offsetting advantage of promoting mating of refuge adults with adults emerging from Bt plants.…”
Section: Spread Of Resistance During Species Invasion or Range Expansionmentioning
confidence: 96%
“…Laboratory selection experiments indicate that western corn rootworm has the ability to develop resistance to all currently commercialized Bt toxins following three to seven generations of selection28293031. Similarly, field-evolved resistance to Cry3Bb1 maize was observed in western corn rootworm populations collected from fields that had been planted to Cry3Bb1 maize continuously for 3 to 7 years14.…”
mentioning
confidence: 97%